A geografia nos anos iniciais do ensino fundamental: um olhar a partir da formação e da prática pedagógica dos professores do município de Alagoa Grande PB - Morais, Jonathas Eduardo Domingos (2014)
The Geography in the early years of elementary school in a perspective from the training and practice of a group of six teachers in Alagoa Grande, PB, is presented as the central theme of this research. We aimed, in this text, to understand the teacher training of the two first years in the elementary education and the pedagogical practice in Geography from the teachers who were subjects in this research, connecting the different formative processes that, respectively, were the Magisterium - through the Normal School - and the degree in Pedagogy, trying to understand how Geography and its teaching methodologies were shown in these different times of training. We sought to know the route of teachers training from their life experiences and training through the contributions of qualitative research in education and elements of life history, that provides to the researcher knowing the past of his subjects over their speeches, the history of life itself and their professional careers, such elements of the choice of the teaching profession and the phases of the training process. A study that enables a better understanding how the teaching methodologies to Geography are treated in training courses, under the reflections of the city where the research took place and how the experiences of this training can be noticed in the teachers practice. A question of major importance in this work is around the issue about the relationship between theory and practice that need to be valued in the training process of teachers. Then, we conclude that many of the gaps and difficulties in everyday practice of teachers are the result of theoretical and methodological problems totally unresolved in the training process. Concerning to Geography in the early years and the relationship of the discipline with these professionals, this is based on the recognition of its importance in students training and, at the same time, in the difficulties discovered in the finding of a good educational practice.